Effects of aging new crop wheat and whole wheat flour on breadmaking quality and glycolipid composition - Mense, Andrew Lawrence (Kansas State University, 2012)
Whole wheat flour has become a popular ingredient in baked goods. Consumers are seeking the added benefits of consuming healthy phytochemicals and bioactive compounds. As the demand for wholemeal flour increases it is important to understand the factors contributing to changes in whole wheat flour breadmaking quality as a function of both wheat and flour age. In wholemeal flour, the lipid composition appears to be a factor causing variable baking quality. Changes that occur in both freshly harvested wheat and milled flour can cause variations in baking quality. Bakers’ attempts to adjust formulations and processes are often unsuccessful. The objective of this study was to determine the effects of aging both new crop wheat and freshly milled flour at 2 different temperatures on baking quality and glycolipid composition. This study aged freshly harvested Overley hard red winter wheat at RT (23˚C) and FZ (-26˚C) for 8, 50, and 91 days before milling. Whole wheat flour baking and lipid extraction studies were performed incrementally over 31 days of flour storage after each milling. Glycolipid structure and amounts were measured using automated electrospray ionization-tandem mass spectrometry. The glycolipids analyzed in this study were DGDG (digalactosyldiglycerol), MGDG (monogalactosylmonoglycerol), MGMG (monogalactosylmonoglycerol), and DGMG (digalactosylmonoglycerol). Both the wheat and flour stored at -26˚C produced larger mean loaf volumes than did the 23˚C treatment for all 3 wheat ages. The FZ and RT DGDG:MGDG ratios were similar over both wheat and flour age so changes to the glycolipid fraction did not appear to be the cause of the significant difference between volumes of bread baked from samples stored at RT and FZ. There was limited change in mean volume over flour age except for an increase at the FZ 91 day point. The DGDG:MGDG ratios were generally unchanged over flour age. Loaf volumes were the same over wheat age except for an unexpected drop during the 50 day wheat study. The corresponding DGDG:MGDG ratios did not show any significant differences over wheat age. The FZ storage temperature might be inhibiting some biochemical change not affecting the glycolipids, leading to higher volumes than the RT storage treatment.
Keywords: Whole wheat flour; Glycolipid; New crop wheat; Flour storage; Wheat aging; Breadmaking; Agriculture, General (0473); Food Science (0359); Home Economics (0386)